Blue-silica by Eu2+-activator occupied in interstitial sites. Issue 91 (9th October 2015) - Kim, Donghyeon; Jin, Yoeng-Hun; Jeon, Ki-Wan; Kim, Sungyun; Kim, Seung-Joo; Han, Oc Hee; Seo, Dong-Kyun; Park, Jung-Chul
<x xml:space="preserve">Abstract</x> A blue-emitting SiO2:Eu2+ compound has been successfully synthesized and characterized.